TINJAUAN PERUBAHAN LAYANAN EKOSISTEM AKIBAT PERLUASAN PERTANIAN DAN PERTAMBANGAN DI DAS TROPIS - La Ode, Rustam; Mulya, Setyardi Pratika Mulya (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2026)
The expansion of agricultural and mining areas in tropical watersheds (DAS) has resulted in changes in ecosystem services (ES), which have been under pressure for decades. This study uses a systematic literature review (SLR) by synthesizing articles published in the Scopus database between 2009 and 2025 using the PRISMA Flow Diagram 2020 framework. The keyword combinations used include